Forest strategy of German Development Cooperation with Africa. (1st March 2006) - Thies, W; Von Pfeil, E; Reiche, M; Drger, D
This article outlines the strategy, main features and priorities of German Development Cooperation in the forest sector in Africa. Details are provided from country case studies in Benin, the Democratic Republic of the Congo, the Republic of the Congo, Cameroon, Madagascar, Tanzania and the Congo basin region.In the forest sector, Germany supports the formulation and implementation of national forest programmes as an overall framework for forest policies in the countries concerned. Intensive support is provided in the fields of forest sector reform, forest certification, community-based forest management, and sustainable management of protected areas. Support is also given to establishing new instruments and strategies designed to secure sustainable financing for protected areas. German Development Cooperation will also strengthen the development of two new approaches in the coming years, namely regional integration as in the Congo basin and Forest Law Enforcement, Governance and Trade (FLEGT).